Citrus Diseases Exotic to Florida: Citrus Leprosis - Ozgur Batuman; Amit Levy; Ajia Paolillo; Kuang-Ren Chung; Ron Brlansky (EDIS, 2020)
This article is one in a series designed to provide important information on the causal agent, symptoms, and transmission of exotic citrus diseases. Disseminating the information about the diseases to the citrus industry may prevent their introduction and spread in Florida. This 5-page document will focus on the exotic viral disease citrus leprosis. This is a major revision of an article originally published in 2006. Written by O. Batuman, A. Levy, P. Sieburth, A. M. Paolillo, K.-R. Chung, and R. H. Brlansky, and published by the UF/IFAS Plant Pathology Department. https://edis.ifas.ufl.edu/pp148